Insulin-like growth factor-1 directly mediates expression of mitochondrial uncoupling protein 3 via forkhead box O4. (June 2019) - Watamoto, Yukiko; Futawaka, Kumi; Hayashi, Misa; Matsushita, Midori; Mitsutani, Mana; Murakami, Kana; Song, Zilin; Koyama, Rie; Fukuda, Yuki; Nushida, Ayaka; Nezu, Syoko; Kuwahara, Akiko; et al.
Abstract: Objective: The objective of our study was to examine the direct action of insulin-like growth factor-1(IGF-1) signaling on energy homeostasis in myocytes. Design: We studied the IGF-1 stimulation of mitochondrial uncoupling protein 3 (UCP3) expression in the HEK 293 derived cell line TSA201, murine C2C12 skeletal muscle myoblasts, and rat L6 skeletal myoblasts. We also investigated the direct effect of IGF-1 on the Insulin/IGF-1 receptor (IGF-1R)/phosphatidylinositol 3 (PI3)-Akt/forkhead box O4 (FOXO4) pathway using a combination of a reporter assay, semi-quantitative polymerase chain reaction, western blotting, and animal experiments. Results: We demonstrated that IGF-1 regulates UCP3 expression via phosphorylation of FOXO4, which is a downstream signal transducer of IGF-1. UCP3 expression increased with activated FOXO4 in a dose-dependent manner. We also examined the functional FOXO4 binding site consensus sequences and identified it as the −1922 bp site in the UCP3 promoter region. UCP3 was also found to be concomitantly expressed with IGF-1 during differentiation of C2C12 myoblasts. Our animal experiments showed that high fat diet induced IGF-1 levels which likely influenced UCP3 expression in the skeletal muscle. Conclusion: Our findings demonstrate that that IGF-1 directly stimulates UCP3 expression via the IGF-1/IGF-1R/PI3-Akt/FOXO4 pathway. Highlights: FOXO4 acts downstream of PI3K-Akt and is involved in IGF-1-mediated energy metabolism. IGF-1 regulates the expression of UCP3 and its impact was greater than that of GH. IGF-1 may play some kind of roles locally in myoblasts differentiation in association with UCP3.